"Being true to oneself": the interplay of responsible leadership and authenticity on multi-level outcomes. Issue 3 (9th February 2021) - Javed, Muzhar; Akhtar, Muhammad Waheed; Hussain, Khalid; Junaid, Muhammad; Syed, Fauzia
Abstract : Purpose: Drawing on stakeholder theory, this study examines the relationship between responsible leadership and its macro-, meso- and micro-level outcomes. Further, this study investigates the moderating role of authenticity on the relationship between responsible leadership and its multi-level effects, i.e. relational social capital, corporate social performance and community citizenship behaviour among employees. Design/methodology/approach: The authors conducted four field studies using the quantitative methodology to test the hypotheses. In study 1 ( N = 236), by adopting a multi-wave and multi-source research design, the authors examine the relationship between responsible leadership, authenticity and relational social capital. In study 2 ( N = 203), by adopting a multi-wave research design, the authors examine the relationship between responsible leadership, authenticity and corporate social performance. In study 3 ( N = 203), by adopting a multi-wave and multi-source research design, the authors examine the relationship between responsible leadership, authenticity and employees' community citizenship behaviour. In study 4 ( N = 257), by adopting a multi-wave and multi-source research design, the authors capture the impact of responsible leadership on outcomes (social capital, corporate social performance and community citizenship behaviour) with a boundary condition of authenticity. Findings: The authors find that responsible leadership enhances relational social capital, improves a firm's social performance and develops community citizenship behaviour among employees. Further, the study finds that authenticity positively moderates the relationship between responsible leadership and its multi-level outcomes. Originality/value: First, it is a maiden study to investigate the multi-level outcomes of RL in a series of three empirical studies. Second, it contributes to RL literature by testing a unique moderating role of authenticity between RL and its multi-level outcomes of relational social capital, corporate social performance and employees' community citizenship behaviour. This study also provides empirical evidence for the multi-level implications of stakeholder theory.